SISTEM INFORMASI KEUANGAN DESA PADA DESA TANJUNG BARU - Kurniasih Kurniasih; Satria Novari; Dian Sri Agustina (Institut Informatika dan Bisnis Darmajaya, 2020)
The Tanjung Baru Village Office is a government agency, the village office has annual revenue and monthly expenditures. For a smooth process of recording and reporting village financial data must also be managed properly, so that village financial records can be reported properly and neatly. Especially those related to confidential finances. One of the best choices for the need for this technology is computers, the technology used as support in processing data effectively and efficiently. With the creation of a Village Financial Information System at the Tanjung Baru Village Office, village officials can easily find information about financial data and hopefully problems that exist in managing village financial data can be minimized, so that data processing can be done more easily, quickly, neatly and efficiently.Data collection is carried out by visiting the place directly by means of interviews, namely conducting interviews or direct questions and answers to the parties or village officials at the Tanjung Baru village office. villages in the village of Tanjung Baru. and references, namely collecting data and information as well as reading and studying documents, or books, as well as other sources related to the creation of Information Systemshis research produces a village financial information system in Tanjung Baru Village using Embarcadeo XE2 which is designed to simplify the processing of data input, data retrieval, and reports